(untitled) (Bioagro, 2025)
Huanglongbing (HLB) is a devastating disease of citrus characterized by yellow spots on the foliage, leaf chlorosis, small and deformed fruits, premature leaf drop, and tree decline which is caused by Candidatus Liberibacter asiaticus. The state of Tamaulipas in Mexico is one of the main producers of Citrus in the country. Given the arrival of HLB in the region, this work focuses on analyzing the individual rhizosphere from symptomatic and asymptomatic orange, lemon, and grapefruit plants cultivated in an orchard in the state. Microbial profiles were analyzed by using a metagenomic approach and bioinformatic tools. The results show that microbial diversity is different between symptomatic and asymptomatic lemon plants. Particularly, the asymptomatic grapefruit plants show the lowest microbial diversity. In general, all Citrus species show differences in their bacterial population structure, identifying groups related to beneficial bacteria, and differences in microbial diversity, according to the presence of HLB symptoms.